High-Throughput Screening for Known Mutations by Automated Analysis of Single Sequencing Reactions - Tom Kristensen; Vessela Nedelcheva Kristensen; Anne-Lise Børresen-Dale (BioTechniques)
This work shows that single sequencing reactions analyzed on an automated DNA sequencer can be an efficient way of screening PCR products for known mutations. We have analyzed a mutation in exon 10 of the human aromatase gene and show that an unambiguous genotype could be elucidated in more than 90% of the analyzed samples. Compared to analysis by full sequencing, 4 times more samples can be analyzed per gel, so that the sample capacity of the gel is approaching that of alternative gel-based methods for genotype analysis. Unlike many of these, the method offers direct identification of the variant sequence position and on-line analysis without the need of postelectrophoretic processing of the gel.